From Indoctrination to Initiation: A Non-Coercive Approach to Faith-Learning Integration. (September 2013) - Reichard, Joshua D.
THIS ARTICLE CONTRIBUTES to ongoing discussions related to the nature, scope, and methods of faith-learning integration. The "initiation" approach developed by Tim McDonough (2011) is adapted to faith-learning integration in an attempt to bridge polarizing discussions regarding indoctrination versus rational autonomy and critical inquiry. The three stages of initiation are reconceived as conflict, creativity, and commitment. Using this model of initiation, teachers in Christian schools may strive toward educating students to be creative and responsive thinkers within the context of the tradition and community of the Christian faith. Ultimately, as the students of today become the scholars of tomorrow, they must be prepared to solve problems, face conflict, and deal with ambiguity. Initiation, as a non-coercive alternative to indoctrination, provides an opportunity to achieve such goals.